DNA and eDNA-based tracking of the North African sharptooth catfish Clarias gariepinus. (June 2020) - Elberri, Aya Ibrahim; Galal-Khallaf, Asmaa; Gibreel, Sarah Emad; El-Sakhawy, Said Fathallah; El-Garawani, Islam; El-Sayed Hassab ElNabi, Sobhy; Mohammed-Geba, Khaled
Abstract: The African sharptooth catfish, Clarias gariepinus, contributes much to the River Nile ecosystem by its high omnivorosity, sturdiness, growth rates, and fecundity. It was globally appreciated as a key fluvial aquaculture species. Yet, it is also one of the top world freshwater aliens. Monitoring the genetic diversity of different economically and ecologically important species as well as development of markers that aid their tracing and abundance are fundamental. This is chiefly due to the growing international threats of environmental pollution, reduction, and loss of biodiversity. Herein, the genetic diversity of C. gariepinus along the River Nile in Egypt was assessed through sequencing of the mitochondrial cytochrome oxidase subunit I (COI). Also, a qPCR assay based on C. gariepinus 16srDNA was developed to assess the species abundance through environmental water DNA samples (eDNA). The results showed low genetic diversity of that species in Egypt. Moreover, its populations exhibited high rates of fixation. Testing its eDNA-based marker resulted in an unambiguous quantitative trend in situ, in agreement with reports of local fishermen. These eDNA signals were strong at least 1 Km upstream to the initial sampling areas, even where no C. gariepinus fishing activities are carried out. This possibly indicated a degree of homogenous species-abundance in each of the studied areas. Finally, the results identified a need for better conservation strategies for C. gariepinus, since its low diversity in the Egyptian River Nile may represent a threat against its persistence under the continuously changing environmental conditions. Moreover, using non-invasive sampling methods, e.g. based on aquatic eDNA quantification, can aid much the detection of areas of abundance of C. gariepinus, especially for both the economic importance it contributes and the invasive power it possesses. Highlights: Clarias gariepinus is one of the top aquaculture species in the world. C. gariepinus was recorded as an invasive species in many rivers. In its natural habitats it shows very low genetic diversity. Mitochondrial DNA markers could be designed for its effective environmental tracking.